ANALISIS PENGGUNAAN CAMPUR KODE DALAM VLOG DAILY DI PLATFOM TIKTOK - Rahayu Widiawanti; Siti Ulfatul Muzayyanah; Sonya Trikandi; Vicky Hidantikarnillah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the use of code-mixing and code-switching in daily vlogs uploaded to the TikTok platform. The phenomenon of using more than one language in digital communication is increasingly common, particularly in social media content targeting diverse audiences. This research employs a qualitative descriptive approach, utilizing data collection techniques that involve observing and recording utterances containing elements of code-mixing and code-switching within TikTok vlogs. The data are analyzed based on the forms and types of these phenomena, as well as the factors influencing their occurrence. The findings are expected to demonstrate that the use of these linguistic phenomena serves not only as a means of communication but also as a strategy to express identity, reinforce messages, enhance content appeal, and adapt to the characteristics of social media audiences. This study is expected to contribute to the field of sociolinguistics, specifically regarding language use in digital communication on the TikTok platform.